Augmented Reality Interfaces in Education Enhancing Learning Experiences Through Interactive Technologies - Endla Purushotham; N Kirthiga; Prasad J Laxmi; P Chellammal; C R Bharathi; G Durgadevi (ITM Web of Conferences)
Augmented Reality (AR) In this step of education: make learning more accessible and enjoyable. This paper aims to explore the implications of AR interfaces for education, highlighting their potential applications for student engagement, knowledge retention, and individualized instruction. The combination of real-time interaction and gamification with spatial visualization enable AR to create active learning environments that can cater to diverse preferences of cognition (Akçayır & Akçayır, 2016). Together, these recent studies (2020–2024) compile a literature review, presenting collective evidence for utility across a wide range of disciplines including STEM education, medical training, and collaborative learning environments, and beyond. This technological development has been underlined by factors such as improved motivation among students, better test scores, and practical experiential learning, illustrating the transformative nature of AR in contemporary education. The research also highlights challenges around technological limitations and cost barriers and recommends solutions for scalable AR integration in classrooms. The work herein will help provide a foundation to build off for future research, curriculum, and practical AR applications across educational institutions internationally.